Muslimpreneur Intentions: Analysis of Family Background - Juliana Juliana; Agus Rahayu; Yuranita Pramudya Wardhani (Islamic Research, 2020)
This research is based on the phenomenon of the problem of high unemployment and low Muslim entrepreneurship in Indonesia. The purpose of this study was to analyze and predict the influence of family background on the intention of the muslimpreneur. The population in this study is students of MA / SMA boarding schools in the city of Bandung. The sampling technique used was a non-probability-accidental sampling technique of 100 people. The method used is causal with a quantitative approach. The data analysis technique used is Patrial Least Square-Structural Equation Modeling (PLS-SEM). The results showed that family background had a positive and significant effect on Muslimpreneur intentions in students of MA / SMA Pesantren in Bandung. The implication in this study is the higher the influence of family background, it will affect the intentions of Islamic entrepreneurship on students.